2022
DOI: 10.1108/md-07-2021-0991
|View full text |Cite
|
Sign up to set email alerts
|

The importance of managerial discretion on managerial ability–firm cash holding nexus

Abstract: PurposeThis paper examines the role of managerial discretion in the relation between managerial ability on the level of corporate cash.Design/methodology/approachConjoining the upper echelons theory's premises and the theoretical framework of cash holdings, we posit that the managerial ability's effect on cash policy varies with managerial discretion using firm-level data. To test the empirical prediction, we employ a linear regression model with fixed effects with a sample of US listed firms from 1980 to 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 114 publications
0
13
0
Order By: Relevance
“…Jebran and Chen (2022) report high ability managers are associated with reduced cash holdings in China. However, Magerakis (2022) find that highability managers are associated with high cash holdings in US This suggests that prior studies have mixed findings on the role of highly able managers in cash holdings. The precautionary motive argues that firm policy is to hold more cash to counter uncertainties or constraints that the business may face due to competition and future projects (Han and Qiu, 2007).…”
Section: Managerial Ability Readability and Debtmentioning
confidence: 73%
See 1 more Smart Citation
“…Jebran and Chen (2022) report high ability managers are associated with reduced cash holdings in China. However, Magerakis (2022) find that highability managers are associated with high cash holdings in US This suggests that prior studies have mixed findings on the role of highly able managers in cash holdings. The precautionary motive argues that firm policy is to hold more cash to counter uncertainties or constraints that the business may face due to competition and future projects (Han and Qiu, 2007).…”
Section: Managerial Ability Readability and Debtmentioning
confidence: 73%
“…A study by Matemilola et al (2018) indicates that experienced and capable managers leverage greater debt to protect the firm's profits from taxation, enhancing debt capital. The review of recent studies investigating managerial ability have focused majorly for developed (Kumar and Zbib, 2022;Khoo and Cheung, 2022;Magerakis, 2022;Haider et al, 2021;Curi and Lozano-Vivas, 2020) or Asian economies (Jebran and Chen, 2022;Phan, 2021;Naheed et al, 2021). Some studies have shown higher ability managers are associated with short-term debt (Khoo and Cheung, 2022;Shang, 2021).…”
Section: Empirical Literature and Hypotheses Developmentmentioning
confidence: 99%
“…Existing research suggests that the influence of slack resources on performance or innovation depends on several factors, including the industry (Daniel et al. , 2004), type of firm (public or private; George, 2005), type of slack (absorbed or unabsorbed; Lee and Wu, 2016) and the degree of managerial discretion (Magerakis, 2022). Nohria and Gulati (1996) demonstrated that both excessive or insufficient slack resources can hinder innovation.…”
Section: Discussion and Contributionmentioning
confidence: 99%
“…and the degree of managerial discretion (Magerakis, 2022). Nohria and Gulati (1996) demonstrated that both excessive or insufficient slack resources can hinder innovation.…”
Section: Tax Planning and Financial Defaultmentioning
confidence: 99%
See 1 more Smart Citation